Analysis of Strength Improvement and Crystallographic Tranformations In an Isothermal Oil Quenched on Martempering AISI 4140 - Sugiantoro , Bambang; Sakuri, Sakuri; Susanto, Tarsono Dwi; Praharto, YB; Sutisna, Utis; Pratiwi, Yuliyanti Dian (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This study aims to maintain the phase change process of 4140 steel at the starting point of martensite (Ms) by adjusting the speed and restraint of the transformation process to prevent the formation of the final martensite (Mf) phase. The use of oil with a constant temperature is able to stabilize the austenite phase into retained austenite (RA). The isothermal cooling (IQ) process uses a cooling chamber controlled by a microcontroller. The partitioning process is isothermal quenching deformation (IQDP) by heating the specimen at 850oC for 20 minutes which is rapidly cooled in oil quenching medium at constant temperature. Oil quenching media is used to hold the cooling rate so that the austenite phase transformation (FCC crystal) to martensite phase (BCT crystal) occurs. The effect of IQDP treatment on phase change, crystal orientation and mechanical properties were analyzed by hardness test, tensile test and SEM. The test results show that IQ treatment on SAE 40 oil is able to increase its tensile strength and modulus of elasticity. The application of isothermal quenching using SAE 40 oil with a constant temperature of 40 oC has been proven to increase the ductility of raw materials from 1226.94 MPa to 1361.77 MPa.